POLA ASUH ORANGTUA DALAM MEMBINA AKHLAK ANAK (STUDI KASUS 5 KELUARGA DI BTN SENGKANG MAS KELURAHAN BENTENGE KECAMATAN WATANG SAWITTO KABUPATEN PINRANG: Pola Asuh Orangtua dalam Membina Akhlak Anak - Al-gifari, Abu Dzar (Jurnal Pendidikan Kreatif, 2023)
Parenting patterns in fostering children's morals at BTN Sekkang Mas, Bentengnge Village, Watang Sawitto District, Pinrang Regency with an indifferent pattern, a democratic pattern, a permissive pattern. There are also children's morals in five different families with very good moral results, quite good, not good and not good. The implication is that first it is hoped that the five families will adopt the right parenting style in accordance with the character of their children first to make it easier to develop children's morals. Second, it is hoped that all parents must be firm in educating children in an environment that is less effective and do not give excessive freedom to children without parental supervision. Third, children are given a lot of knowledge and strong religious provisions, so that they are not adversely affected, and the parents themselves must be good at supervising their children.